PERAN ANALIS KREDIT DALAM PEMBERIAN KREDIT PADA PT. BPR CAHAYA KHATULISTIWA SEJAHTERA PERAN ANALIS KREDIT DALAM PEMBERIAN KREDIT PADA PT. BPR CAHAYA KHATULISTIWA SEJAHTERA - Saraswati, Resha; Jaurino (Program Studi Akuntansi Universitas Panca Bhakti, 2024)
This study investigates the role of credit analysts in the credit provision process at PT. BPR Cahaya Khatulistiwa Sejahtera and the impact of changes in Non-Performing Loans (NPL) on the bank's performance. Using qualitative methods and the 5C analysis technique, the research reveals the strengths and weaknesses in the bank's credit provision procedures. While the bank adheres to prudential principles and incorporates the 5C principles in credit assessment, challenges in archival practices have led to inefficiencies. To address these issues, it is recommended that the bank implement a structured digital archiving system and provide training programs in human resource management. These measures are expected to improve credit provision, operational efficiency, customer service, and the bank's reputation, emphasizing the critical role of credit analysis in the bank's overall operations.